(untitled) (Scientific journal of the Fergana State University, 2025)
The article is devoted to the study of lexical ways of verbalizing the concept "head/голава/жла" in English and Russian. The work considers the main lexemes expressing this concept, as well as their semantic features and variability in context. The analysis is carried out on the material of stable expressions, metaphors and phraseological units, demonstrating cultural and cognitive differences in the use of the concept "head" in two languages. Particular attention is paid to the differences in metaphorical models and figurative meanings, which allows for a deeper understanding of the relationship between language and thinking.